Draft genome assembly for the purple-hinged rock scallop (Crassadoma gigantea) - Hayley Goss; Paige Miller; Susan F. Zaleski; Robert J. Miller; Donna M. Schroeder; Henry M. Page (BMC Genomic Data)
Abstract Objectives This genomic sequence for the purple-hinged rock scallop, Crassadoma gigantea, is a substantial improvement over currently available NCBI genomes for the species and will be an important resource for future genomic research, including ongoing and future population genetic studies. Purple-hinged rock scallops are found along the west coast of North America with a native range from Northern Alaska to Northern Mexico and found to depths of up to ~ 50 m. While not commercially harvested, this species is harvested recreationally and is a candidate of interest for aquaculture and conservation. Data description The draft genome for C. gigantea is 817.3 MB, containing 7,183 scaffolds (contig N50 = 287.9 Kb, scaffold N50 = 965.5 Kb). Benchmarking Universal Single-Copy Orthologs (BUSCO) analysis using the 5295 genes in the mollusca_odb10 database had a 93.3% completeness value (92.7% single, 0.6% duplicated). Repeat elements made up 32.23% of the genome. MetaEuk reference-based discovery identified and annotated 23,409 unique protein sequences. Functional annotation was completed by Pannzer2. This assembly will contribute to the ongoing population genetic research on this species.